Over-Agglomeration and its Effects on Sustainable Development: A Case Study on Istanbul - Abdullah Kaya (44754) (2018)
Inequality, in any form and dimension, is a major damaging factor for sustainable development. One of the essential drivers of inequality is the over-agglomeration and congestion in a certain region. The reasons for the agglomeration are well documented, such as knowledge-spillovers, access to supply and demand markets, availability of skilled labor, and good infrastructure. However, over-agglomeration in a region, mainly triggered by poor planning and mismanagement of resource allocation, may also become a barrier for sustainable development. The over-agglomeration generally results in undesired negative effects impeding the economic, social, and environmental development any further, even causing irreversible social and environmental issues. Following the big-push model, a theoretical model is proposed to consider the negative effects of increasing rent prices due to over-agglomeration first on the industrial development of a country. This is then followed by a case study of Istanbul as a megacity and its effects on Turkey’s sustainable development through industrial, social, and ecological aspects. Istanbul has been the main industrial and economic center of Turkey as the city further expanded rapidly in the last 50 years in terms of population and urbanization. This over-agglomeration has resulted in very high rent prices in the city compared to the rest of Turkey, which affected the country’s industrialization. The over-agglomeration in Istanbul has also created significant economic imbalances and income-inequalities within the city and across Turkey. The environmental degradation, the loss of forest area, and very high air and noise pollution were other results of the city’s rapid expansion and over-agglomeration. These industrial, social, and environmental dynamics pose serious challenges to Turkey’s sustainable development as long as over-agglomeration in Istanbul persists or even aggravates further. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su11010135